Novelty Before or After Word Learning Does Not Affect Subsequent Memory Performance - Biel, Davina; Bunzeck, Nico (Frontiers in Psychology, 2019)
In humans, exposure to novel images and exploration of novel virtual environments before the encoding of words improved subsequent memory performance. Animal studies revealed similar effects of novelty, both before and after learning, and could show that hippocampus dependent dopaminergic neuromodulation plays an important role. Here, we further investigated the effects of novelty on long-term memory in humans using a novel paradigm employing short sequences of nature movies presented either before or at two time-points after learning of unrelated words. Since novelty is supposed to release dopamine into the hippocampus, we hypothesized that novelty exposure primarily affects hippocampus-dependent memory (i.e. recollection) but not hippocampus-independent memory (i.e. familiarity). We tested 182 healthy human subjects in three experiments including a word-learning task followed by a one-day delayed recognition task. Importantly, participants were exposed to novel (NOV) or familiar movies (FAM) at three time points: (experiment 1) directly after encoding of the word list, (experiment 2) 15 minutes after encoding, (experiment 3) 15 minutes prior to encoding. As expected, novel movies were perceived as more interesting and led to better mood. During word recognition, reaction times were faster for remember as compared to familiarity responses in all three experiments, but this effect was not modulated by novelty. In contrast to our main hypothesis, there was no effect of novelty – before or after encoding – on subsequent word recognition, including recollection and familiarity scores. Therefore, an exposure to novel movies without an active task does not affect hippocampus-dependent and hippocampus-independent long-term recognition memory for words in humans.